Melvin Dietzel and Larry Oeffner examining replacement parts in Dow's Instrument Department - Dow Chemical Company (1948)
General view of Melvin Dietzel (kneeling) and Larry Oeffner examining the stock supply of replacement parts in the Dow Chemical Company's Instrument Department. Established in 1926, the Instrument Department was responsible for the installation and maintenance of the assorted apparatus necessary to manage the plant's production facilities and processes. The department notably maintained accurate standards for temperatures, voltage, resistance, flow and pressures against which the plant's instruments were regularly calibrated and checked for accuracy.
Keywords: Machine parts--Maintenance and repair; Industries; Scientific apparatus and instruments; Machine parts--Inspection; Machine parts--Standards; Machine parts; Employees; Dow Chemical Company; Oeffner, Larry; Dietzel, Melvin